2017
DOI: 10.1002/adfm.201702261
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Tunable Photonic Bandgaps in Self‐Organized 3D Nanostructure of Polymer‐Stabilized Blue Phase I Modulated by Voltage Polarity

Abstract: Electrically responsive photonic crystals represent one of the most promising intelligent materials for technological applications in optoelectronics. In this research, a polymer-stabilized blue phase (PSBP) I film with the self-organized 3D nanostructure is fabricated, and an electrically tunable photonic bandgap (PBG) is achieved. Interestingly, the large-scale shift of the PBG covering the entire visible spectrum is found to be asymmetric and can be modulated by the polarity and magnitude of bias voltage. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 53 publications
0
69
1
1
Order By: Relevance
“…Among various types of ordered nanoarchitectures, photonic liquid crystals (PLCs) of 2D nanomaterials have attracted recent attention owing to the ability of dynamically interacting with the light of interest to achieve brilliant reflection colors (11). Generally, the color of PLCs originates from the periodic structures with long-range positional ordering, such as lamellar or helical arrangement (12)(13)(14)(15)(16)(17). In particular, lamellar structure is one of the most studied designs for fabricating photonic materials of 2D building blocks due to the structural similarity to natural nacre and pearls (18).…”
mentioning
confidence: 99%
“…Among various types of ordered nanoarchitectures, photonic liquid crystals (PLCs) of 2D nanomaterials have attracted recent attention owing to the ability of dynamically interacting with the light of interest to achieve brilliant reflection colors (11). Generally, the color of PLCs originates from the periodic structures with long-range positional ordering, such as lamellar or helical arrangement (12)(13)(14)(15)(16)(17). In particular, lamellar structure is one of the most studied designs for fabricating photonic materials of 2D building blocks due to the structural similarity to natural nacre and pearls (18).…”
mentioning
confidence: 99%
“…Lorenz et al reported that the operating voltage of the H-PNLC cell fabricated by coPNLCs with suitable concentrations of the mesogenic and the non-mesogenic monomers is around 8-12 V [46]. Other polymer materials can also be investigated for fabricating H-PNLC/coPNLC cells to decrease their operation voltages [1,2,10,[48][49][50]. Overall, the optimized photopolymerization to fabricate the H-PNLC cell meeting the criteria for real display applications should be further investigated [1,3,4].…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, LCs exhibiting BPs have attracted a lot of attention due to their potential applications in several areas ranging from displays to photonic applications. [280][281][282][283][284][285] The BPs are isotropic Kerr medium, but under an electric field they become anisotropic. There are certain advantages of using BPs in a given application, especially for diffraction gratings: they do not require an alignment layer, which simplifies fabrication process; they present very fast response time, in the order of microseconds and, because of the medium's optical properties, the grating is polarization independent.…”
Section: Blue Phase Lc Gratingsmentioning
confidence: 99%